A Magnetically Drivable Nanovehicle for Curcumin with Antioxidant Capacity and MRI Relaxation Properties. Issue 37 (30th July 2014) - Magro, Massimiliano; Campos, René; Baratella, Davide; Lima, Giuseppina; Holà, Katerina; Divoky, Clemens; Stollberger, Rudolf; Malina, Ondrej; Aparicio, Claudia; Zoppellaro, Giorgio; Zbořil, Radek; Vianello, Fabio
Abstract Curcumin possesses wide‐ranging anti‐inflammatory and anti‐cancer properties and its biological activity can be linked to its potent antioxidant capacity. Superparamagnetic maghemite (γ‐Fe2O3), called surface‐active maghemite nanoparticles (SAMNs) were surface‐modified with curcumin molecules, due to the presence of under‐coordinated FeIII atoms on the nanoparticle surface. The so‐obtained curcumin‐modified SAMNs (SAMN@curcumin) had a mean size of 13±4 nm. SAMN@curcumin was characterized by transmission and scanning electron microscopy, UV/Vis, FTIR, and Mössbauer spectroscopy, X‐ray powder diffraction, bulk susceptibility (SQUID), and relaxometry measurements (MRI imaging). The high negative contrast proclivity of SAMN@curcumin to act as potential contrast agent in MRI screenings was also tested. Moreover, the redox properties of bound curcumin were probed by electrochemistry. SAMN@curcumin was studied in the presence of different electroactive molecules, namely hydroquinone, NADH and ferrocyanide, to assess its redox behavior. Finally, SAMN@curcumin was electrochemically probed in the presence of hydrogen peroxide, demonstrating the stability and reactivity of bound curcumin.